ANALISIS STUDI KELAYAKAN BISNIS PADA PANGKALAN GAS LPG “RANA” DI DESA CIBATU KECAMATAN CIKARANG SELATAN KABUPATEN BEKASI (Ditinjau dari Aspek Teknis, Aspek Pasar dan Pemasaran, dan Aspek Keuangan) - Retna Widianingsih; R.R Wening Ken Widodasih; Kurbandi Satpatmantya BR (Jurnal Ilmiah Global Education, 2023)
In Indonesia, the use of gas is a more economical alternative, one example is the conversion of kerosene to 3kg LPG. According to BPS statistical data, the use of LPG in Indonesia exceeds 83.36% of households using LPG for cooking. The purpose of this study is to assess the business feasibility of the "Rana" LPG gas base both from a non-financial and financial perspective. Non-financial variables, such as market and marketing characteristics, as well as technical variables, are used in the analysis. While the financial analysis tools used to determine whether or not a business is feasible to develop use Payback Period (PP), Break Event Point (BEP), Net Present Value (NPV), and Internal Rate of Return (IRR) analysis. This study uses a qualitative data collection approach such as interviews, observation, and documentation. Based on the findings of non-financial aspects such as market and marketing aspects, as well as technical aspects, the "Rana" LPG Gas Base is feasible to develop, while the findings of the financial aspects show that the "Rana" LPG Gas Base Business is feasible to run, with the calculation results producing a Payback Period (PP) of 1 year 11 months 2 weeks, Net Present Value (NPV) of Rp. 23,461,447, Break Even Point (BEP) of Rp. 461,447,.